Ultra-thin Chip Technology and Applications - Burghartz, Joachim.; Burghartz, Joachim. (Springer New York : Imprint: Springer, 2011)
Ultra-thin Chip Technology and Applications edited by: Joachim N. Burghartz Ultra-thin chip technology has the potential to provide solutions for overcoming bottlenecks in silicon technology and for leading to new applications. This book shows how very thin and flexible chips can be fabricated and used in many new applications in microelectronics, microsystems, biomedical and other fields. It provides a comprehensive reference to the fabrication technology, post processing, assembly, characterization, modeling and applications of ultra-thin chips. •Provides a comprehensive overview of the challenges in ultra-thin chip fabrication, post processing, properties and applications by leaders in the field sharing their newest results and ideas; •Compares strengths and weaknesses of three generic fabrication processes for ultra-thin chips; •Describes electronic, mechanical, optical, and thermal properties of ultra-thin chips that are different from those of conventional, thick chips; •Shows that thin chip technology and its applications represents a new paradigm in silicon technology.